Factors for Formation and Regulation of the Ukrainian Population’s Incomes in the Context of the Middle Class Formation - Т. S. Ihnatenko (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
A key criterion for identification o f the middle class is income level enabling for the households ’ consumption by the socialy acceptable standards. The share o f middle class can grow only in parallel with the increasing polulation incomes. The article’s objective is to study incomes o f the Ukrainian population in the context o f the middle class formation and analyze regulatory mechanisms pertaining to the populations' incomes and wages in Ukraine. The study is based on the official statistical data for 2012-2016 (population’s incomes and employment, nominal sages in hryvnya and dollar equivelant). The Kaitz index is calculated for Ukraine by data for 2015-2017. An extendive review o f the data obtained from the sample survey o f householdes on self-assessment o f their incomes, conducted in January 2017, is given. The analysis o f factors behind the formation o f population’s incomes in Ukraine gives evidence o f the low life standards in Ukraine, the wide income gap and the threatening scales ofpoverty. The main source o f the population incomes in Ukraine is salary, with the insignificant share o f income from property. While the nominal wage was growing year-to-year in 2012-2016, its dollar equivalent reduced twofold. According to the data of the abovemenationed sample survey, only 0.7% o f city households and 0.3% o f rural ones classified themselves in the middle class. Ukrainian still lacks appropriate mechanisms for regulation o f incomes and wages through differentiated taxation ofvarious population strata; the domestic stock market needs to be built in as way to ensure the increasing incomes from property; the rate o f minimal wage should be better justified.